МОНГОЛ ТӨРИЙН ТҮШМЭЛ - Ц.Ганболд (Politology, 2023)
Mongolians’ are a nation with a hundreds of years’ culture of statecraft tradition and a rich source of wisdom inherited from its’ ancestry. In ancient Mongolian teaching on statecraft of “Арван буянт номын цагаан түүх‘’, literally translated as “The White History”, there are plenty of well described features of nobleman which still keeps its’ importance on how to select statesman and public officials in contemporary political life.